Security control for nonlinear systems under quantization and Round-Robin protocol subject to deception attacks - Wu, Bo; Chang, Xiao-Heng (ISA transactions, 2022)
This paper is concerned with the security control problem for the nonlinear systems with the effects of quantization, communication protocol and deception attacks based on the Takagi–Sugeno (T–S) fuzzy model. The measurement output and control input signals are quantized by dynamic quantizers simultaneously, and the quantized signals are transmitted through the communication channels scheduled by Round-Robin (RR) protocol. Moreover, two Bernoulli processes are utilized to characterize the deception attacks occurring on the different channels respectively. The mode-dependent observer-based controller and dynamic quantizers are designed such that the security in probability of the closed-loop system with the prescribed quadratic cost index can be guaranteed. Then, sufficient design conditions are obtained for the controller gains and quantizers’ parameters based on the linear matrix inequalities (LMIs) approach. In the end, a numerical example is carried out to demonstrate the validity of the proposed method. •Security control problem is studied for nonlinear system based on T–S fuzzy method.•Dynamic quantization is considered for the measurement output and control input.•A novel framework is introduced for the impacts of RR protocol and deception attacks.•Sufficient LMIs-based conditions are established for the controller and quantizers.